Pengaruh High Perfomance Human Resource Management Practices Terhadap Organizational Citizenship Behavior Yang Dimediasi Work Engagement - Handayani, Ririn; Kurniadi, Yudho Oktano; Seswandi, Agus (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This study uses a quantitative method with a descriptive and explanatory survey approach. The research was conducted at the Land Office of Kampar Regency, with the aim of examining the effect of high-performance human resource management practices on organizational citizenship behavior (OCB) mediated by work engagement. The population of this study consists of all employees of the Land Office of Kampar Regency, totaling 144 people. Based on this population size, according to the Krejcie and Morgan table (1970), the sample size for this study is 103 people. The sampling method used in this study is Systematic Random Sampling. All respondents will be used to collect primary data related to the variables, which will be gathered through a questionnaire with a 5-point Likert scale. The high-performance HR practices variable is measured using indicators from Wei et al. (2011). The work engagement variable is measured using indicators from Schaufeli and Bakker (2004). Organizational citizenship behavior is measured based on the OCB-C Checklist by Spector, P. E., Bauer, J. A., & Fox, S. (2010). All data collected will be analyzed using Structural Equation Modeling (SEM) with the Smart PLS 3.0 analysis tool. This study found that (a). High-performance HR practices have a positive effect on organizational citizenship behavior; (b). High-performance HR practices have a positive effect on work engagement; (c). Work engagement has a positive effect on organizational citizenship behavior; and (d). Work engagement mediates the effect of high-performance HR practices on organizational citizenship behavior.